Retrospective analysis of chronic injuries in recreational and competitive surfers: Injury location, type, and mechanism - Furness, J.; Hing, W.; Abbott, A.; Walsh, J.; Sheppard, J. M.; Climstein, M. (International Journal of Aquatic Research and Education, 2014)
Only two studies have reported on chronic musculoskeletal surfing injuries. They found over half of the injuries were non-musculoskeletal, but did not consider mechanisms of injury. This study identified the location, type, and mechanisms of chronic injury in Australian recreational and competitive surfers using a crosssectional retrospective observational design. A total of 1,348 participants (91.3% males, 43.1% competitive surfers) reported 1,068 chronic injuries, 883 of which were classified as major. Lower back (23.2%), shoulder (22.4%), and knee (12.1%) regions had the most chronic injuries. Competitive surfers had significantly (p < .05) more lower back, ankle/foot, and head/face injuries than recreational surfers. Injuries were mostly musculoskeletal with only 7.8% being of non-musculoskeletal origin. Prolonged paddling was the highest frequency (21.1%) for mechanism of injury followed by turning maneuvers (14.8%). The study results contribute to the limited research on chronic surfing injuries.